Evaporation of a sessile droplet on flat surfaces: an axisymmetric lattice Boltzmann model with consideration of contact angle hysteresis - Zhang, Chaoyang (2022)
Droplet evaporation is a widely encountered heat and mass transfer phenomenon. Due to its 3D in nature, it is challenging to simulate the complex 3D droplet evaporation process. Here, we propose an axisymmetric lattice Boltzmann (LB) model to simulate the dynamics of contact line motion during sessile droplet evaporation on a flat heated surface, taking contact angle hysteresis into consideration. We demonstrate that this LB model can numerically simulate the evaporation processes of sessile droplet evaporation processes undergoing constant contact angle (CCA), constant contact radius (CCR), and mixed modes sequentially. The classical D2-law for droplet surface mass transfer is confirmed numerically by using the case of a floating droplet evaporation, thereby proving that the axisymmetric LB model is capable of 3D simulation. Our simulated results on temporal variations of contact radius, contact angle are found in good agreement with two different sets of literature experimental data. Specifically, we compute the local mass transfer rate on the droplet surface from the simulated velocity field to show that the evaporation rate near the triple-phase contact region is much higher than that at the droplet apex region, with the peak heat flux occurring near the location of the dynamic contact line. The contact angle fluctuates with stick-slip motion are found during the CCA stage of the evaporation process at higher substrate temperatures. Additionally, we analyse the non-quasi-equilibrium evaporation mode and contact line slip velocity on substrates surface at higher temperatures.